Financial Deepening and Sustained Economic Growth in Nigeria: What Nonlinear Models Reveal - Kalu, Ebere Ume; Okoyeuzu, Chinwe R.; Okechukwu, Elizabeth U.; Ukpere, Wilfred Isioma (Journal of Reviews on Global Economics, 2019)
Motivated by the desire to expose a possible nonlinearity and non-proportionality in linking financial deepening and economic growth, we investigated the finance-growth nexus from a linear and nonlinear perspective using dataset from Nigeria for 1981: Q1 to 2017: Q4. Using the Autoregressive Distributed Lag (ARDL) and Nonlinear Autoregressive distributed Lag (NARDL) models, and it was found that economic growth tends to adjust nonlinearly to financial deepening than it does linearly. This is expected to guide policy makers towards ensuring that the linearity and nonlinearity polarity of the finance-growth nexus are always factored-in while formulating policies relative to driving sustained growth through financial deepening.